The improved Boer goat - Malan, S.W. (2000)
The history, origin and characteristics of the South African Boer breed of goats are reviewed. The development was carried out by a handful of farmers in the eastern Cape, particularly in the district of Somerset East. The prototype for the breed was selected from several existing breeds of goats in South Africa in order to achieve the present functional characteristics and type. The Boer goat is a hardy breed with great capacity for adaptation and an exceptional ability to withstand and resist diseases. The Boer goat is highly fertile, conception rate is about 90%, kidding rate about 189% and fecundity rate 210%. Weaning weight at 120 days averages 29 kg. Boer doe produces enough milk to raise twins easily. Boer goat yields falvousome, succulent, tender and tasty lean meat of high quality, particularly during the young stage. Boer goat is able to maintain a high level of production up to 10 years of age. Details on breed standards of the Boer goat are presented. Numerous countries had imported Boer goats from South Africa including USA, New Zealand, Australia, Germany, Israel, France and more recently China.